A checklist of the praying mantises of Peru: new records, one new genus (Piscomantis gen. n.) and biogeographic remarks (Insecta, Mantodea) - Rivera, Julio; Vergara-Cobián, Clorinda (Zootaxa, 2017)
We present a preliminary checklist of the praying mantises (Insecta: Mantodea) of Peru. A total of 67 species are reported, nine of which constitute new records from that country. The following new nomenclatural procedures are introduced: Musoniella margharethae Battiston and Picciau, 2008 is transferred to Musonia as Musonia margharethae (Battiston and Picciau, 2008) (comb. n.), and Phyllovates brevicollis Orofino, Ippolito and Lombardo, 2006 is considered a new synonym (syn. n.) of Pseudovates peruviana (Rehn, 1911). A new genus, Piscomantis gen. n., is established to accommodate Galapagia peruana Beier, 1935, which is now referred to as Piscomantis peruana (Beier, 1935) (comb. n.). Ten species are removed from the Peruvian mantis fauna and two nomina nuda are proposed. An overview of the biogeography and ecology of Peruvian praying mantises is presented.